Indian painting from cave temples to the colonial period - Cummins, Joan 1965- (MFA Publications, 2006)
"From refined portraits of resplendent maharajas to earthy depictions of divine rogues cavorting with milkmaids, Indian miniature paintings depict the world as it should be: radiant, plentiful and passionate. These manuscript illustrations combine vibrant color with exquisite delicacy, offering immediate impact while also rewarding lengthy examination. This fascinating volume presents the art form for non-specialists, surveying the most notable styles and periods of Indian painting and offering an introduction to the legends and historic personalities that inspire its entertaining subjects. The text covers such diverse topics as scriptures written on palm leaves, likenesses of favorite animals, images inspired by music, techniques and materials, and Indian reactions to European art. The Museum of Fine Art Boston's collection of Indian paintings, assembled by the esteemed scholar A. K. Coomaraswamy, is justly renowned as one of the finest in the world, and Indian Painting, one of the only readily available comprehensive histories of the subject, is the first book since Coomaraswamy's seminal catalogues of the 1920s to draw so extensively on the MFA's collection. It includes 120 of the most remarkable pieces, many of which are reproduced in color for the first time"--Publisher's description